On creating conditions for the acquisition of Discourse specific literacies in English Studies: the value of integrating language studies and literary studies in English departments - Mgqwashu, Emmanuel Mfanafuthi (South African Journal of Higher Education, 2016)
Students’ acquisition of Discourse specific literacies associated with the field of English Studies depends on the extent to which English departments view the role of language studies discipline in their intellectual pursuit. The paper is not arguing for English departments to introduce language teaching in an instrumentalist approach, a pedagogy which is ‘…all but terminally consigne[s] English to the level of a technical language stripped of expressive and aesthetic characteristics and denuded of any critical or self-conscious dimension’ (Said 1994, 369). Instead, by means of empirical, qualitative data, the paper argues for ‘a pedagogy for an ‘enriched’ English [which] will clearly need to attend to the complex manner in which structure, content and function inter-relate in the production of effective, literate English’ (Wallace 2003, 93). It shows that the acquisition of ‘literate English’ by students in English departments will be possible if language studies and literary studies get integrated in pedagogic practice. The paper draws from Narrative-style interviews and Systemic Functional Linguistics theory as the research instrument and theoretical framing for data collection and analysis, respectively.